PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PRODUKSI SAWI DI KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Etik Purnami; Shorea Khaswarina; Suardi Tarumun (Indonesian Journal of Agricultural Economics, 2012)
Mostly Indonesian people depend their life on agricultural sector. Vegetable is one ofagriculture comodity which can give big contribution to economics development if itmanaged optimally. The productivity of vegetable influenced by natural factor (climate,soil, etc), fertilizer, pestiside, capital, and human resource. This research is aimed atidentifying the influence of production factor to mustard production and to analyze theallocation efficiency of the production factor usage in mustard farm using the purposivesampling method with 40 mustard farmer in Maharatu village, Marpoyan Damaisubdistrict. The estimated result with Cobb-Douglas production function indicated that theproduction of mustard farm in Maharatu village were influenced by seed, organic fertilizer,urea, NPK, pestisde, and labour in level 99%. The NPM/Px value for seed and urea is ≥ 1,it means the usage both of that factors can be increased. The value of NPM/Px for NPK,pestiside and labour usage is not important to reach economic efficiency condition and getthe maximum benefit.Keyword: mustard, production factor, cobb-douglas, economic efficiency